MINIMALISIR KETAKUTAN MASYARAKAT MELALUI KEGIATAN SOSIALISASI DAN EDUKASI PENTINGNYA VAKSINASI COVID-19 - Ani Maulani; Rahma Ari Widihastuti; Wahyuni Lia Wulandari; Putri Wulandari; Muhlis Safi’i; Ayu Lestari (LPPM Universitas Bina Bangsa, 2021)
Covid-19 has spread in Indonesia since 2020 and has caused greater casualties and material losses. So that it has implications for social, economic, and community welfare aspects. The government has implemented several policies such as Large-Scale Social Restrictions but the virus still does not end. Until finally the Covid-19 vaccination was held, but instead received several pro and con responses from the public, not even a few were afraid because of some hoax information circulating. Socialization and education activities about Covid-19 are very much needed in these circumstances. In socialization activities, many people were enthusiastic and felt helped by the information conveyed, but there were also people who still refused to be vaccinated against Covid-19 and still believed that Covid-19 was a conspiracy